THE ROLE OF CORPORATE SOCIAL RESPONSIBILITY AND GOOD CORPORATE GOVERNANCE IN ENHANCING THE VALUE OF MINING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Fajar Rakasiwi Syamsuddin (Jurnal Ekonomi, 2023)
This study aims to examine the role of Corporate Social Responsibility and Good Corporate Governance in enhancing the value of mining companies listed on the Indonesia Stock Exchange during the period of 2019 to 2021. The population of this study is all mining companies listed on the stock exchange, with a sample of 10 companies determined using purposive sampling technique with specific considerations. The research method used is quantitative with an associative causal model and SPSS 24 application as the analysis tool. Based on the results of the F-test, both Corporate Social Responsibility and Good Corporate Governance variables play a role in increasing the value of the company, and the t-test shows that each variable has a partial role in enhancing the value of the company.